Monosodium Glutamate Maintains Antioxidant Balance in the Neuro-Retinal Axis of Male Wistar Rats - Nalugo, Halima; Ninsiima, Herbert Izo; Kasozi, Keneth Iceland; Nabirumbi, Ritah; Osuwat, Lawrence Obado; Nassan, Mohamed A.; Matama, Kevin; Ssempijja, Fred; Batiha, Gaber El-Saber (Research square, 2021)
Purpose: Information on monosodium glutamate (MSG) safety in the eye-brain axis remains scarce. The objective of the study was to establish changes in calcium (Ca2+) concentrations, catalase activity, Malondialdehyde (MDA) levels and identify any major histological changes associated with parenteral and feed supplementation of MSG in male Wistar rats. This is important to guide policy on human consumption of food additives. Methods: Thirty adult male Wistar rats were divided into 5 groups (n = 6) for a period of one month. Group I and IV were treated with MSG 6g/kg and 60 mg/kg subcutaneous, while groups II and III at 5% and 2% MSG feed supplement. Group V was the control group treated with normal saline (no MSG). The eye and brain were analyzed for Ca2+, catalase, MDA levels and histological analysis was done using Hematoxylin and Eosin staining. Results: Calcium levels in the eye was reduced at high (6g/kg/day and 5% s.c) MSG treatments while in the brain these remained constant. Since Ca2+ plays a crucial role in catalase activity, levels of catalase were not affected in eye-brain axis. MDA levels were elevated at high MSG treatments and no structural changes in the retina of the eye and no damage were found in the brain. Conclusion: MSG maintained catalase levels, Ca2+ and no structural changes were observed in the eye and brain.
Keywords: Monosodium glutamate in the eye-brain axis; Eye-brain health; MSG myths; Food additives in the eye and brain